Meta-analysis of the association between MALAT1 rs619586 A>G polymorphism and cancer risk. Issue 7 (July 2020) - Ni, Wenwen; Wang, Xinyu; Sun, Yuqi; Gao, Xueren
Objective: This study aimed to systematically assess the effect of the metastasis associated lung adenocarcinoma transcript 1 ( MALAT1 ) long noncoding RNA rs619586 polymorphism on cancer risk. Methods: We conducted a literature search of the PubMed, Embase, and China National Knowledge Internet databases to identify relevant studies, and calculated the pooled odds ratios (ORs) and 95% confidence intervals (CIs) for the retrieved studies using RevMan software. Results: Nine eligible studies including 5968 cases and 7439 controls were included in the meta-analysis. The pooled results showed that MALAT1 rs619586 polymorphism was significantly associated with cancer risk [(AG + GG) vs. AA: OR = 0.88; GG vs. (AG + AA): OR = 0.64; GG vs. AA: OR = 0.63; AG vs. AA: OR = 0.91; G vs. A: OR = 0.87]. However, subgroup analyses based on ethnicity and cancer type showed significant associations between MALAT1 rs619586 polymorphism and cancer risk in Asians and for cancers other than hepatocellular carcinoma, but not for Caucasians and hepatocellular carcinoma. Conclusions: MALAT1 rs619586 polymorphism may play a role in cancer risk. However, further studies are needed to confirm these findings.